STUDYING THE GENETIC DIVERSITY OF SOME SOLANUM MELONGENA L. VARIETIES USING MOLECULAR TECHNOLOGY - H. M. AL-Jaf, idrees; K. Alalwani , Anmar (University of Thi-Qar Journal of agricultural research, 2024)
The study performed a genetic fingerprinting investigation of ten eggplant varieties (Solanum melongena L.) using random amplified polymorphic DNA (RAPD) markers based on polymerase chain reaction (PCR) and calculated the percentage of genetic distance. Using five RAPD primers in the fall of 2024 in the Seed Inspection and Certification Department's biotechnology labs.The maximum discriminatory ability was 25.53% and 31.42% with primer OPC-05, while polymorphisms of 74.75% were found across all genotypes. The efficiency percentage of each primer was 25.53%. The findings demonstrated that the lowest genetic dimension (0.679) between Varieties S6 and S3 and the highest percentage of similarity (0.666) between Varieties S10 and S3 are correlated. The ten varieties were found to be divided into A and B, the two primary groups. Cluster A was further subdivided into two subgroups, A1 and A2, and branch A1 contained two secondary groups, the first of which contained two genotypes: S7 and S4, and the second was S1 and S9. Group A2 contained both types, S5 and S2, while cluster (B) was divided into two clusters, with both strains present in the first cluster, S3, S6, and S10, while the variety (S8) remained isolated from the other varieties.